Hydroquinone-O,O'-diacetic acid ('Q-linker') as a replacement for succinyl and oxalyl linker arms in solid phase oligonucleotide synthesis. - Pon, R T (1997)
When hydroquinone-O,Ooffiacetic acid is used as a linker arm in solid phase oligonucleotide synthesis, the time for NH4OH cleavage of oligodeoxy- or oligoribonucleotides is reduced to only 2 min. This allows increased productivity on automated DNA synthesizers without requiring any other modifications to existing reagents or synthesis and deprotection methods. The Q-linker may also be rapidly cleaved by milder reagents such as 5% NH4OH, potassium carbonate, anhydrous ammonia, t-butylamine or fluoride ion. However, the Q-linker is sufficiently stable for long-term storage at room temperature without degradation and no loss of material occurs during synthesis. The linker is also reasonably resistant to 20% piperidine/DMF, 0.5 M DBU/pyridine and 1:1 triethylamine/ethanol. The Q-linker can therefore serve as a general replacement for both succinyl and oxalyl linker arms.